2008
DOI: 10.1016/j.inffus.2006.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic integration of classifiers for handling concept drift

Abstract: Abstract. In the real world concepts are often not stable but change with time. A typical example of this in the biomedical context is antibiotic resistance, where pathogen sensitivity may change over time as new pathogen strains develop resistance to antibiotics that were previously effective. This problem, known as concept drift, complicates the task of learning a model from data and requires special approaches, different from commonly used techniques that treat arriving instances as equally important contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
115
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(116 citation statements)
references
References 28 publications
0
115
0
1
Order By: Relevance
“…One example in the real world is spam filtering, where only some particular types of spam may change with time, while the others could remain the same. In these cases, the accuracy of global models may fall, even if they still could be good experts in the stable parts of the data [2].…”
Section: A Ensembles For Concept Drift: Local and Diversementioning
confidence: 99%
See 1 more Smart Citation
“…One example in the real world is spam filtering, where only some particular types of spam may change with time, while the others could remain the same. In these cases, the accuracy of global models may fall, even if they still could be good experts in the stable parts of the data [2].…”
Section: A Ensembles For Concept Drift: Local and Diversementioning
confidence: 99%
“…Apart from filtering for recommendation systems, concept drift is a central problem in many dynamically changing and non-stationary environments, including medicine [2], industry [3], education [4], and business [5]. In these dynamic scenarios the challenge is to process, in (near) real-time, large highspeed data streams in order to adapt the learning model by combining what has been learned in the old concept with the fresh information corresponding to the new concept.…”
Section: Introductionmentioning
confidence: 99%
“…Tsymbal et al propose a strategy based on local concept drift [80,81]. They argue that many real-world scenarios of concept drift are in fact local phenomenon, relegated to a specific region of the feature space.…”
Section: Concept Locality Based Approachesmentioning
confidence: 99%
“…The last group consists of algorithms that incorporate a set of classifiers (Wang et al 2003;Stanley 2003;Tsymbal et al 2008). It has been shown that a collective decision can increase classification accuracy because the knowledge that is distributed among the classifiers may be more comprehensive.…”
Section: Related Workmentioning
confidence: 99%